Automated Feeding Fish Menggunakan Raspberry Pi, Webcam dan Sensor Suhu Berbasis IoT - Irma Salamah; Ciksadan Ciksadan; Nadila Savira Makarau (BEES: Bulletin of Electrical and Electronics Engineering, 2020)
The problem that often occurs in fish feeding is when the owner travels far away. With the Internet of Things technology can facilitate the maintenance of fish in the form of automatic feeding tools that can facilitate the owner. In this study, the author will build tools and applications that can provide fish feed automatically. This tool was built with the Raspberry Pi as its main controller which is equipped with a servo motor as an opening for fish feed, a temperature sensor to detect aquarium temperature, an ultrasonic sensor as a detection of feed residue, aquarium monitoring using a webcam, a relay as a controller for water filters and water heaters in the aquarium. Overall this tool is associated with Android-based applications. When feeding fish can be done in two ways, namely based on a schedule that has been set in the application and directly by pressing the button on the application. In the process of making this tool utilizing the Python programming language, while the application is built with Android Studio with Java and XML programming languages. Overall integration between tool and application data is sent to the server by storing the database in MySQL. It is hoped that this research can work functionally to facilitate fish feeding activities.